Influenza A and Febrile Seizures - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2006)
Predisposing factors and characteristics of febrile seizures in children with influenza A infection were studied in children hospitalized with febrile seizures between January and July 2005 at Tuen Mun Hospital, Hong Kong.